2007
DOI: 10.1159/000109968
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prohepcidin and Hepcidin-25 with Erythropoietin Response and Ferritin in Hemodialysis Patients

Abstract: Hepcidin is a key regulator of iron metabolism. In this study, we examined whether measurement of hepcidin is useful in assessing recombinant human erythropoietin (rHuEPO) responsiveness in regular hemodialysis (HD) patients in a cross-sectional fashion. We examined the association between serum prohepcidin, a prohormone of hepcidin, and rHuEPO dosage and the rHuEPO/hemoglobin (Hb) ratio in 75 HD patients. We also semiquantatively measured the peak intensity of serum hepcidin-25, the major form of mature hepci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
91
3
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 52 publications
19
91
3
5
Order By: Relevance
“…In the recent paper of Bradbury et al, [23] CRP appeared to be an independent predictor of greater erythropoietin requirements. In our study, hyporesponsive patients had significantly higher hsCRP than responders as in the study of Kato et al [24] We also found lower serum cholesterol, LDL, and albumin, as well as higher hsCRP and proinflammatory cytokines, suggesting MIA syndrome, a finding not confirmed by Kato et al [24] They observed no difference in hepcidin-25 (measured using SELDI-TOF), whereas in our study, a tendency to higher hepcidin levels (measured by RIA) were found. Similarly, in the study of Shinzato et al, [25] no significant difference in serum prohepcidin was found between HD patients with rHuEPO-resistant anemia and HD patients without anemia and iron deficiency.…”
Section: Discussionsupporting
confidence: 78%
“…In the recent paper of Bradbury et al, [23] CRP appeared to be an independent predictor of greater erythropoietin requirements. In our study, hyporesponsive patients had significantly higher hsCRP than responders as in the study of Kato et al [24] We also found lower serum cholesterol, LDL, and albumin, as well as higher hsCRP and proinflammatory cytokines, suggesting MIA syndrome, a finding not confirmed by Kato et al [24] They observed no difference in hepcidin-25 (measured using SELDI-TOF), whereas in our study, a tendency to higher hepcidin levels (measured by RIA) were found. Similarly, in the study of Shinzato et al, [25] no significant difference in serum prohepcidin was found between HD patients with rHuEPO-resistant anemia and HD patients without anemia and iron deficiency.…”
Section: Discussionsupporting
confidence: 78%
“…Interestingly, hepcidin levels were correlated with ferritin in these subjects (1,4). Theoretically, increased hepcidin levels may reduce intestinal iron absorption and iron recycling from monocytes (24), decreasing serum iron available for the erythropoiesis (28) and the therapeutic effect of ESAs and i.v.…”
mentioning
confidence: 97%
“…I ncreased serum levels of hepcidin, the novel iron hormone inhibiting iron absorption from enterocytes and iron recycling from macrophages, have recently been reported in patients with end-stage renal disease (ESRD), and hypothesized to contribute to the alterations of iron metabolism and anemia of ESRD (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its effect on iron metabolism; hepcidin may contribute to rhEPO resistance through a direct inhibitory effect on erythroid progenitor proliferation and survival [5]. Other studies revealed contradictory results; Kato et al [19] found hepcidin levels were not different between rhEPO-responsive and rhEPO resistant dialysis patients, whereas Ford et al [20] found no relationship of hepcidin with rhEPO dose. Over expression of hepcidin in animals impairs the response to even supra physiological doses of rhEPO [21].…”
Section: Discussionmentioning
confidence: 99%